(untitled) (Comprehensive Journal of Science, 2025)
This research examines the tourism attraction components of the city of Sabratha and evaluates their impact on tourism demand using both quantitative and qualitative indicators. An integrated methodology was adopted, combining quantitative analysis through questionnaires and qualitative analysis through interviews. The study analyzed the effect of tourism demand for each tourism attraction component separately, in addition to identifying the level of local tourism demand in the city of Sabratha and the challenges facing tourism development there. The findings indicate that Sabratha possesses unique tourism attraction components; however, these alone are not sufficient to ensure stable tourism demand. Political factors may outweigh the quality of internal tourism resources. The future success of tourism in Sabratha depends on the development of integrated tourism services and smart marketing strategies based on the city’s global archaeological value. Achieving this would transform Sabratha from an archaeological site into a sustainable tourist destination that contributes to local economic developme